2020
DOI: 10.3390/agronomy10111837
|View full text |Cite
|
Sign up to set email alerts
|

Studying Gene Expression in Irradiated Barley Cultivars: PM19L-like and CML31-like Expression as Possible Determinants of Radiation Hormesis Effect

Abstract: Gamma (γ)-irradiation of plants at low doses can provoke a broad range of growth-stimulating effects. In order to reveal universal target genes that are involved in molecular pathways of radiation hormesis establishment, we studied nine barley cultivars for their tolerance to γ-irradiation of seeds. Four morphological traits were assessed in barley seedlings after γ-irradiation of seeds at 20 Gy. Nine cultivars were sorted according to the sensitivity to irradiation as γ-stimulated, “no morphological effect”, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…SOG1 is a member of a large NAC (NAM, ATAF1/2, and CUC2) family of transcription factors in plants and a list of 167 barley NAC domain containing proteins was published, highlighting HORVU.MOREX.r3.7HG0670800 (alias HORVU7Hr1G042420) as the most likely homolog of Arabidopsis ANAC008 ( At SOG1) 24 . On contrary, another gene HORVU.MOREX.r3.6HG0590960 (alias HORVU6Hr1G053540) was suggested as HvSOG1 based on upregulation upon DNA damage treatment 25 . Therefore, we analyzed SOG1 in barley in more detail.…”
Section: Resultsmentioning
confidence: 99%
“…SOG1 is a member of a large NAC (NAM, ATAF1/2, and CUC2) family of transcription factors in plants and a list of 167 barley NAC domain containing proteins was published, highlighting HORVU.MOREX.r3.7HG0670800 (alias HORVU7Hr1G042420) as the most likely homolog of Arabidopsis ANAC008 ( At SOG1) 24 . On contrary, another gene HORVU.MOREX.r3.6HG0590960 (alias HORVU6Hr1G053540) was suggested as HvSOG1 based on upregulation upon DNA damage treatment 25 . Therefore, we analyzed SOG1 in barley in more detail.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, transcriptomics is the key to investigating gene function in targeted physiological mechanisms qualitatively and quantitatively [ 57 ]. Detecting hormetic stimulation at the transcript level can be achieved by analyzing the differential expression of known genes on small (~20) [ 58 , 59 , 60 ] and very large scales using microarray technology (~50,000) [ 61 ] or by completely sequencing the RNA from a sample as in next-generation and third-generation sequencing [ 62 , 63 , 64 ].…”
Section: Data In Plant Hormesis Researchmentioning
confidence: 99%
“…Radiobiological studies of barley responses to IR showed that this stress factor can be successfully used to identify molecular pathways involved in barley adaptation to abiotic stressors [23][24][25]. Numerous papers are focused on barley's adaptive responses to γ-radiation, as it is the radiation type more available for research [9,[23][24][25][26][27][28], where growthstimulating and growth-inhibiting dose-dependent effects are considered in molecular details.…”
Section: Introductionmentioning
confidence: 99%
“…Radiobiological studies of barley responses to IR showed that this stress factor can be successfully used to identify molecular pathways involved in barley adaptation to abiotic stressors [23][24][25]. Numerous papers are focused on barley's adaptive responses to γ-radiation, as it is the radiation type more available for research [9,[23][24][25][26][27][28], where growthstimulating and growth-inhibiting dose-dependent effects are considered in molecular details. Several studies of proton and electron radiation effects on barley plants are also available in the literature, demonstrating both positive and negative impacts on its growth, development, and productivity, alone or in combination with other stress factors [29,30].…”
Section: Introductionmentioning
confidence: 99%